NATIONAL AND INTERNATIONAL REGULATIONS ON PROPERTY RIGHTS - BANU, Cristiana Ecaterina (Journal of Advanced Research in Law and Economics, 2016)
Indissolubly connected to people’s life, being part of it, property has represented a problem of continuous feature, having an especially important place within the economical, socio-political and philosophical sciences. The study of this article herein is trying to make a brief analysis of one of the most significant and present civil right institutions and namely the institution of property, as real main right. The Romania’s accession to the EU on 1st January 2007 imposes structural changes at the economy level, as well as in the entire Romanian society. Thusly, as consequence of obtaining the statute of member-state of the European Union with full rights, it is necessary to analyse the regulation on the property right in Romanian, European and International Law, with all consequences resulting from here.
Keywords: property, property right, freedom and fundamental rights